OFR-109-85 Advancement Of Cab And Canopy Design And Use In Coal Mines - W. W. Aljoe (The National Institute for Occupational Safety and Health (NIOSH), 1981)
The use of protective canopies can result in canopy roofing and/or serious restrictions to operator comfort and vision. To document this experience, BCR conducted a field study of cab and canopy design and application which resulted in a catalog of 164 canopy designs and an analysis of field data which showed no simple relationship between working height and canopy-related problems. The relationship also involves (1) machine frame height, (2) mine floor undulations, (3) operator compartment dimensions, (4) canopy design and location on the machine. Data analysis indicates (1) present technology does not always permit successful application of canopies in working heights below 42 inches, and (2) development of satisfactory low-coal canopies is doubtful. The basic conclusion of the study is that future R&D studies should be directed at development of alternative protection systems and remote mining methods.